2018
DOI: 10.1016/j.celrep.2018.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cell Cycle Status Underlie Transcriptional Heterogeneity in the HSC Compartment

Abstract: Hematopoietic stem cells (HSCs) are considered a heterogeneous cell population. To further resolve the HSC compartment, we characterized a retinoic acid (RA) reporter mouse line. Sub-fractionation of the HSC compartment in RA-CFP reporter mice demonstrated that RA-CFP-dim HSCs were largely non-proliferative and displayed superior engraftment potential in comparison with RA-CFP-bright HSCs. Gene expression analysis demonstrated higher expression of RA-target genes in RA-CFP-dim HSCs, in contrast to the RA-CFP r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…It was initially thought that specific transcriptional networks of individual HSCs were the major determinants for driving specific lineages ( Kee, 2011 ; Novershtern et al., 2011 ). However, similar to a recent study ( Lauridsen et al., 2018 ), we found that the transcriptional networks for myelopoiesis or lymphopoiesis were similar in HSCs/MPPs after BCG vaccination or Mtb infection. Rather, the magnitude of several key pathways, including IFN-I and heme/iron metabolism, differed considerably.…”
Section: Discussionsupporting
confidence: 90%
“…It was initially thought that specific transcriptional networks of individual HSCs were the major determinants for driving specific lineages ( Kee, 2011 ; Novershtern et al., 2011 ). However, similar to a recent study ( Lauridsen et al., 2018 ), we found that the transcriptional networks for myelopoiesis or lymphopoiesis were similar in HSCs/MPPs after BCG vaccination or Mtb infection. Rather, the magnitude of several key pathways, including IFN-I and heme/iron metabolism, differed considerably.…”
Section: Discussionsupporting
confidence: 90%
“…Functional enrichment profiling of genes upregulated in L1-C iHPCs clusters 50 was consistent with previous scRNA-SEQ studies showing a large contribution of cell cycle genes to transcriptional heterogeneity observed in differentiating hematopoietic cells 51 , particularly stem and progenitor cells 52,53 . L1-C CD42a + iHPCs, clusters 1 and 3 were enriched in cell cycle-related biological processes, whereas cluster 7 showed broad enrichment in myeloid-and especially Mk/plateletassociated genes.…”
Section: Scrna Seq Identifies Novel Deregulated Pathways In Runx1 +/-supporting
confidence: 89%
“…There are many reasons for differences in gene expression among cells, with arguably the most obvious candidates being differences in regulation among cell types, and differences in cell cycle phase among cells [11][12][13]. Cell type and cell cycle phase, while interesting to study directly, are often considered confounders in single cell studies that focus on other factors influencing gene expression [14][15][16], such as genotype, treatment [17], or developmental time [5,18]. The ability to characterize, correctly classify, and correct for cell type and cell cycle phase are therefore important, even in studies that do not specifically aim to study either of these factors.…”
Section: Introductionmentioning
confidence: 99%